INVESTIGAÇÃO CRÍTICA DA QUALIDADE DA ENERGIA ELÉTRICA DISPONÍVEL NA SUBESTAÇÃO DO CENTRO DE LANÇAMENTO DE ALCÂNTARA - Cruz, Harnoldo Castro (2012)
This work investigates electromagnetic disturbances that affect the power quality of the Alcântara Launch Center (CLA), supplied by the local power distribution utility company and the self-generation of the Center, emphasizing disturbances for sensitivity of electrical ground support equipment, variations in voltage and short-term transients. From a bibliographical study, the main electromagnetic phenomen apresented are related to the power quality, showing the causes, consequences and suggestions for mitigation of these events, including the reduction of inrush current, based on standard norms related to the subject. The monitoring was performed using an accurate monitoring equipment during a two-rocket launch campaign, for a better contextualization ofvoltage variations associated to short-term transients. From the records and gathered data, critical events and power quality indices associated to the distribution utility and to the generation set were analyzed, as well as the severe disturbances characterized by CBEMA curve. The results provided subsidies to improve and reduce the effects of voltage short-term and transient events. Thus an operating procedure for special processes is proposed, which can be used both in the aerospace sector as in organizations that have their processes associated to power quality.